VR Use in Online Learning for Higher Education in Indonesia - Kustandi, Cecep; Fadhillah, Dini Nur; Situmorang, Robinson; Prawiladilaga, Dewi S; Hartati, Sofia (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This research leads to the object of learning in network-based learning programs application of the use of VR in online learning for students in Higher EducationThis research is located in the Education Technology study program, Universitas Negeri Jakarta, Indonesia. This study focuses on learning theories, learning methods and learning models used in technology to improve learning outcomes in class. This method used explanatory sequential mixed methods research. Field trials were conducted for students, with a total of 12 students and field trials would be conducted for students with a total of 30 people in 2018. Data collection through interviews of 15 students and 3 lecturers for 40 minutes. The results showed that using VR can foster motivation to learn to develop student skills in simulating learning models and learning can be efficient and effective. VR can also enhance students for teaching practices and train students to innovate learning models used in technology.